Genetic variability of Arthurdendyus triangulatus (Dendy, 1894), a non-native invasive land planarian - Roberts, David M; Boag, Brian; Hunter, Fraser; Tarlton, Jamie; Mackenzie, Katrin; Neilson, Roy (Zootaxa, 2020)
Arthurdendyus triangulatus (Dendy, 1894) is a land planarian native to New Zealand which has become established in the United Kingdom and the Faroe Islands during the last 60 years. The species has become prevalent and widely established in Scotland mediated by human activity mostly through the exchange of plants and associated soil. As a predator of earthworms, concerns regarding both the direct impact on earthworm abundance and diversity and the indirect impact on those birds and mammals that have earthworms as a primary dietary component led to A. triangulatus being the subject of both national and EU regulation. Whilst much is known regarding the ecology of A. triangulatus there is a significant knowledge gap regarding the genetic variability of the species. Using four DNA target regions cytochrome oxidase (CoI), elongation factor (EF), internal transcribed spacer region (ITS-1) and large subunit (LSU), we characterised the genetic variability of A. triangulatus populations across its full geographic range in Scotland and included a few populations from New Zealand, England and Northern Ireland. Two DNA regions, ITS-1 and CoI, revealed inter-population variability yielding well supported genetic structure in predominantly Scottish populations. We also identified considerable intra-specific and intra-individual heterogeneity in both ribosomal and mitochondrial regions, including the prevalence of pseudo-gene nuclear encoded mitochondrial DNA (Numt), the latter not previously reported for Platyhelminthes. Furthermore, given the presence of multiple ITS-1 haplotypes in individual specimens of A. triangulatus it is not possible to make definitive comment to support previously published findings that A. triangulatus was subjected to multiple introductions into the UK.